The Impact of Zakat Programs on Local Economic Development (A Case Study of Dompet Dhuafa) - M. Rizqi Zain Pratama; Hartutik Hartutik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to comprehensively examine the impact of zakat programs on strengthening the economy at the local level, focusing on the case study of Dompet Dhuafa, an Islamic philanthropy institution. The research emphasizes how the implementation of zakat, particularly in the form of productive zakat, can drive improvements in the quality of life and economic independence for the beneficiaries (mustahik). The method used in this study is a qualitative approach through phenomenological methods, which allows the researcher to explore real experiences and perceptions of the mustahik after receiving zakat assistance. The findings indicate that the productive zakat provided by Dompet Dhuafa is not only consumptive, but This has an impact on increasing income, expanding business capacity, and even opening up new job opportunities in the surrounding environment. In addition to economic impacts, zakat also contributes to the social and psychological aspects of the mustahik, such as growing self-confidence, improving financial literacy, and motivation to become independent. This study also highlights that zakat governance at Dompet Dhuafa is carried out professionally and systematically, encompassing assessment stages, data verification, distribution of assistance, and long-term mentoring. The use of digital technology in the reporting and monitoring process further strengthens transparency and effectiveness in the distribution of zakat. This digitization also expands the reach of beneficiaries and strengthens the relationship between muzakki, zakat institutions, and mustahik. Overall, the research results conclude that good, accountable, and targeted zakat management can provide a real contribution to local economic development also serves as initial capital for starting and developing small businesses. Which is inclusive and sustainable. Productive zakat has proven to be a strategic instrument in economically empowering mustahik, even encouraging them to eventually become muzakki. Thus, zakat plays an important role in creating a self-sufficient, fair, and highly competitive societal order.